Enhanced Antitumor Immunity Through T Cell Activation with Optimized Tandem Double-OX40L mRNAs - Deng Z; Tian Y; Wang J; Xu Y; Liu Z; Xiao Z; Wang Z; Hu M; Liu R; Yang P (International Journal of Nanomedicine)
Zhuoya Deng,1– 3,* Yuying Tian,1,* Jing Wang,1 Yongru Xu,1 Zherui Liu,3,4 Zhaohui Xiao,1 Zhaohai Wang,1 Minggen Hu,1 Rong Liu,1 Penghui Yang1 1Faculty of Hepato-Pancreato-Biliary Surgery, Institute of Hepatobiliary Surgery, the First Medical Center, Chinese PLA General Hospital, Beijing, People’s Republic of China; 2Beijing Youan Hospital, Capital Medical University, Beijing, People’s Republic of China; 3The Fifth Medical Center, Chinese PLA General Hospital, Beijing, People’s Republic of China; 4Peking University 302 Clinical Medical School, Peking University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Penghui Yang; Rong Liu, Email ypenghuiamms@hotmail.com; liurong301@126.comPurpose: The tumor immune microenvironment (TIME) is often dysfunctional and complex, contributing to tumor metastasis and drug resistance. This study investigates the use of mRNA-based cancer agents as promising tools to combat and reverse refractory TIME conditions.Methods: We optimized and engineered an mRNA cancer agent encoding double tandemly repeated sequences of the T cell costimulator Oxford 40 ligand (diOX40L). The diOX40L mRNAs were encapsulated into lipid nanoparticles (LNPs) for effective delivery. The research explored its safety and antitumor effects through a series of in vivo and in vivo experiments.Results: Our results demonstrate that diOX40L mRNAs efficiently express increased levels of OX40L proteins. The optimized diOX40L mRNA cancer agent generated potent immune costimulatory signals within the TIME, leading to decreased tumor growth and improved survival compared to the original sequence agent. OX40L expression in subcutaneous tumors promoted CD4+ and CD8+ T cell activation, resulting in heightened IFN-γ and IL-2 secretion and robust immune responses. Combination therapy involving PD-1 antibodies and diOX40L substantially enhanced antitumor efficacy, with increased infiltration of activated CD4+ and CD8+ T cells.Discussion: In conclusion, our findings highlight the therapeutic potential of the optimized diOX40L mRNA cancer agent in cancer treatment and its potential as an innovative alternative to protein-based therapies. The study underscores the significance of mRNA-based agents in modulating the immune microenvironment and enhancing antitumor responses.Keywords: tumor immunotherapy, tumor immune microenvironment, OX40L mRNA, malignant tumor, lipid nanoparticles